Skin Mast Cells Contribute to Sporothrix schenckii Infection - Jiao, Qingqing; Luo, Ying; Scheffel, Jörg; Geng, Peng; Wang, Yuhan; Frischbutter, Stefan; Li, Ruoyu; Maurer, Marcus; Zhao, Zuotao (Frontiers in Immunology, 2020)
Background:Sporothrix schenckii (S. schenckii), a dimorphic fungus, causes sporotrichosis. Mast cells (MCs) have been described to be involved in skin fungal infections. The role of MCs in cutaneous sporotrichosis remains largely unknown. Objectives: To characterize the role and relevance of MCs in cutaneous sporotrichosis. Methods: We analyzed cutaneous sporotrichosis in wild-type (WT) mice and two different MC-deficient strains. In vitro, MCs were assessed for S. schenckii-induced cytokine production and degranulation after incubation with S. schenckii. We also explored the role of MCs in human cutaneous sporotrichosis. Results: WT mice developed markedly larger skin lesions than MC-deficient mice (> 1.5 fold) after infection with S. schenckii, with significantly increased fungal burden. S. schenckii induced the release of tumor necrosis factor alpha (TNF), interleukin (IL)-6, IL-10, and IL-1β by MCs, but not degranulation. S. schenckii induced larger skin lesions and higher release of IL-6 and TNF by MCs as compared to the less virulent S. albicans. In patients with sporotrichosis, TNF and IL-6 were increased in skin lesions, and markedly elevated levels in the serum were linked to disease activity. Conclusions: These findings suggest that cutaneous MCs contribute to skin sporotrichosis by releasing cytokines such as TNF and IL-6.